Median Nerve Variations at the Carpal Tunnel, an Anatomical Study - Aamir, Shabnum; Ghani, Fazal; Khan, Barirah; Tariq, Zayad; Ambreen, Sadaf; Khattak, Munila Shabnum (ADVANCES IN BASIC MEDICAL SCIENCES, 2020)
Background: Awareness of anatomical variations of median nerve at wrist is essential in the treatment of carpal tunnel syndrome to avoid any unfavourable outcomes. To study anatomical variation of median nerve in patients undergoing carpal tunnel release surgery in Khyber Teaching Hospital Peshawar, Khyber Pakhtunkhwa. Methodology: This cross-sectional study was conducted on 200 out-door patients with moderate and severe carpal tunnel syndrome visiting outpatient department of Khyber Teaching Hospital. The duration of study was 10 months. The median nerve was carefully observed during each surgery under local anaesthesia. Any variation in the morphology of median nerve and its branches within and around carpal tunnel was noted and Lanz classification of the median nerve anatomical variations at the wrist was applied. Data was recorded and presented as percentages. Results: Out of 200 patients, normal anatomy of median nerve was found in 189 (94.5%) patients. The variation observed was high bifurcation (division) of median nerve before passing beneath flexor retinaculum. It was observed in 11 (5.5%) cases, out of which 4 (2%) were accompanying persistent median artery, Lanz classification Group 3. Conclusion: The study shows anatomical variation in the course of median nerve in the form of high division of nerve. This variation is also observed with a persistent median artery. Keywords: Carpal tunnel syndrome, Median nerve, Transverse carpal ligament